2cos*2x-3=2

Simple and best practice solution for 2cos*2x-3=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2cos*2x-3=2 equation:


Simplifying
2cos * 2x + -3 = 2

Reorder the terms for easier multiplication:
2 * 2cos * x + -3 = 2

Multiply 2 * 2
4cos * x + -3 = 2

Multiply cos * x
4cosx + -3 = 2

Reorder the terms:
-3 + 4cosx = 2

Solving
-3 + 4cosx = 2

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 4cosx = 2 + 3

Combine like terms: -3 + 3 = 0
0 + 4cosx = 2 + 3
4cosx = 2 + 3

Combine like terms: 2 + 3 = 5
4cosx = 5

Divide each side by '4osx'.
c = 1.25o-1s-1x-1

Simplifying
c = 1.25o-1s-1x-1

See similar equations:

| x^2+x^3=100 | | y^2+8y-384=0 | | 9x+4y=3x+8 | | 6x-12y+15u=0 | | 3+-3*6+-2=0 | | 5a-6=4a+5 | | 0.04x+0.06y=2500 | | 10-3(4a-3)=2(3a-4)-9 | | 25x+50x=10000 | | abx=3abx+xb^2+xa^2+bx^2+ax^2+a^2b+b^2a | | x^3-68x-308=0 | | x^2+521x+223=0 | | 8d-2h+16=0 | | -x+6x-8=3x+7 | | 40-x^2=o | | 4t+3d=9 | | 8x-11=-9 | | 18x^2-(3x-2)(6x-1)=-17 | | F(X)=x^2-48 | | 4=2a-6 | | s=-1s | | (x+1)[2x+1]=x+0.5(1)+1.000000001 | | (x+1)[2x+1]=x+0.5(1) | | (x+1)[2x+1]=x+0.5 | | (x+1)[2x+1]=x+0.25 | | (9-6i)*m=9-6i | | (x+1)[2x+1]=x | | (9-6i)*m=m | | m=6/m | | x=0x | | 60=x-134 | | 8x^2-35x-38=0 |

Equations solver categories